Modeling the sintering trajectories of MgAl2O4 Spinel. (October 2021) - Kerbart, Gabriel; Harnois, Christelle; Marinel, Sylvain; Manière, Charles
Abstract: Controlling microstructure and density of MgAl2 O4 spinel is a crucial step in the elaboration of industrial ceramics products. Understanding the sintering characteristics is a key issue to optimize the mechanical and optical properties. In this paper, Olevsky's sintering model is used to simulate the sintering trajectories of spinel. The densification and grain growth behaviors were identified via ramping and interrupted isothermal cycles highlighting the final stage sintering mechanisms change. The sintering trajectory model is intended to be a powerful numerical tool for sintering optimizations. Graphical abstract: Image, graphical abstract